Molecular characterization of dengue virus serotype 1 infections in French travelers from Africa between 2013 and 2019 - Fourié, Toscane; Durand, Guillaume André; Touret, Franck; Piorkowski, Géraldine; Dubot-Pérès, Audrey; de Lamballerie, Xavier; Leparc-Goffart, Isabelle; Grard, Gilda (Frontiers in Virology, 2023)
Laboratory confirmed dengue virus (DENV) infections in Africa are scarcely reported. In this study, we report 18 DENV serotype 1 (DENV-1) infections in French patients, diagnosed by the French National Reference Center for Arboviruses, that had recent travel histories in Africa. Our analyses revealed two cases, one from the Niger in 2018 and one from the Republic of the Congo in 2016, where dengue fever had not been previously reported, as well as one case from Mauritania in 2015, where serotype 1 had not been reported. These data support the trend of DENV expansion outside of its well established tropical and subtropical environment towards the arid deserts of the Sahel. Phylogenetic analyses suggest that a single monophyletic DENV-1 lineage currently circulates in West Africa, having spread from East Africa after its original importation from Asia. Our study provides a better understanding of DENV dynamics in Africa and underlines the importance of surveillance of travel-acquired infections.